Indexing of Meteorological Drought - Каверіна, К.; Костирко, І.; Олійник, Ростислав Васильович (Київський національний університет імені Тараса Шевченка, 2019)
Drought is a serious extreme climatic event that negatively affects the physical environment and water systems causing disruptions in the hydrological cycle of the region. This is a stochastic natural hazard caused by persistent rainfall scarcity. The life cycle of the drought begins with a meteorological phenomenon, and further influence is realized throughout the hydrological cycle. Adequate measures are needed to respond and mitigate the various effects of drought. Developing and implementing drought mitigation and response strategies requires understanding the various indicators used to study drought. Drought characteristics are an important condition that allows both retrospective analysis and forward planning – risk assessment. Thus, it is necessary to objectively identify the events of drought by time, duration, scale and severity of manifestation. This can be implemented with integrated indicators that involve the main characteristics of the drought. More than 150 drought indices have now been proposed, some of which are perceived as operational information used to characterize drought through maps at regional and national levels. By quantifying the level of severity and announcing the onset and end of drought, drought indices are now assisting in a variety of operations, including early warning, drought monitoring and contingency planning. Despite their diversity and continuous development, it is important to provide a comprehensive overview of the available weather indicators, which highlights their differences and studies their trends and which can be used in a special given manner regional climate.

Посуха – це екстремальна кліматична подія, яка негативно впливає на фізичне середовище та системи водних ресурсів викликаючи порушення в гідрологічному циклі даного регіону. Це стохастична природна небезпека, що спричинена постійним дефіцитом опадів. Життєвий цикл посухи починається з метеорологічного явища, а подальший вплив реалізується в усьому гідрологічному циклі. Необхідні адекватні заходи для реагування та пом’якшення різних наслідків, спричинених посухами. Розробка та реалізація стратегій пом’якшення посухи та реагування на неї вимагає розуміння різних показників, які використовуються для дослідження посухи. Характеристики посухи є важливою умовою, що дозволяє здійснювати як ретроспективний аналіз, так і перспективне планування – оцінку ризику. Таким чином, потрібен засіб об’єктивної ідентифікації подій посухи за часом, тривалістю виникнення, масштабом та суворістю прояву. Це можливо реалізувати за допомогою інтегральних показників, в які залучені основні характеристики посухи. Наразі запропоновано вже понад 150 індексів посухи, деякі з них сприймаються як оперативна інформація, що використовується для характеристики посухи за допомогою карт на регіональному та національному рівнях. Шляхом кількісного визначення рівня суворості та оголошення початку та кінця посухи індекси посухи на даний час допомагають у різних операціях, включаючи раннє попередження, моніторинг посухи та планування надзвичайних ситуацій. Зважаючи на їх різноманітність та постійний розвиток, важливо забезпечити всебічний огляд наявних показників метеорологічної посухи, що підкреслює їх різницю та вивчає тенденцію їх розвитку і які можуть бути використані з врахуванням особливостей регіонального клімату.
Індексація метеорологічної посухи
Селянинов Г.Т. (1958) Происхождение и динамика засух. Г.Т. Селянинов //Засухи в СССР. Их происхождение повторяемость и влияние на урожай. Под ред. А.И.Руденко.-Л.Гидрометеоиздат,1958.-с.5-30 Хохлов В.М., Єрмоленко Н.С. Просторово-часова мінливість посух в східноєвропейському секторі в умовах глобальних змін клімату. Український гідрометеорологічний журнал, 2012, №11.- с.128-134 Agwata, J. F. (2014). A Review of Some Indices used for Drought Studies. Civil and Environmental Research, 6(2), 14–21. Akshaya Prabha A.V., Pandiyarajan G.K., Ravikumar G. Meteorological and Hydrological Drought Assessment – A Review. International Journal of Scientific & Engineering Research Volume 8, Issue 10, October-2017.97 ISSN 2229-5518 Allen, R. G., L. S. Pereira, D. Raes, and M. Smith, 1998: Crop evapotranspiration: Guidelines for computing crop water requirements. FAO Irrigation and Drainage Paper 56,300 pp Bachmair S., Stahl K., Collins K., Hannaford J., Acreman M., Svoboda M., Overton I. C. (2016). Drought indicators revisited: the need for a wider consideration of environment and society. Wiley Interdisciplinary Reviews: Water, 3(4), 516–536. https://doi.org/10.1002/wat2.1154 Doan Quang Tri, Tran Tho Dat, Dinh Duc Truong. Application of Meteorological and Hydrological Drought Indices to Establish Drought Classiﬁcation Maps of the Ba River Basin in Vietnam. Hydrology 2019, 6, 49; doi:10.3390/hydrology6020049. Gibbs W.J. and Maher J.V., Rainfall. deciles as drought indicators, Bureau of Meteorology Bulletin No. 4, Commonwealth of Australia, Melbourne, Australia. Handbook of Drought Indicators and Indices WMO-No1173.-2016 Hayes, M.J., Drought indices, national Drought Mitigation Center, University of Nebraska-Lincoln http://www.drought.unl.edu/whatis/indices.htm#spi Indiana Department of Natural Resources. (2015). Review of available drought indices. Review of Available Drought Indices, (Cmi). Retrieved from http://www.in.gov/dnr/files/ws-Final_droughtindices.pdf Ionita M., Tallaksen L., KingstonD., Stagge J., Laaha G., Van Lanen H., Scholz P., Chelcea S., Haslinger K. The European 2015 drought from a climatological perspective. Hydrol. Earth Syst. Sci., 21, 1397–1419, 2017 www.hydrol-earth-syst-sci.net/21/1397/2017/ doi:10.5194/hess-21-1397-2017 ІPCC. Climate change 2007: Impacts, adaptation and vulnerability. In Contribution of Working Group II to the Fourth Assessment, Report of the Intergovernmental Panel on Climate Change; Parry, M.L., Canziani, O.F., Palutikof, J.P., van der Linden, P.J., Hanson, C.E., Eds.; Cambridge University Press: Cambridge, UK, 2007; Available online: https://www.ipcc.ch/report/ar4/wg2 Keyantash, J. and Dracup, J.A. (2002) The Quantification of Drought: An Evaluation of Drought Indices. Bulletin of the American Meteorological Society, 83, 1167 Kogan F. N., Contribution of remote sensing to drought early warning. Proceedings of an expert group meeting held on Warning Systems for Drought Preparedness and Drought Management. Lisbon, Portugal, 5-7 September. McKee, T.B., N.J. Doesken and J. Kleist, 1993: The relationship of drought frequency and duration to time scale. In: Proceedings of the Eighth Conference on Applied Climatology, Anaheim, California,17–22 January 1993. Boston, American Meteorological Society, 179–184. Niemeyer, S. New drought indices, options méditerranéennes. Sér. A: Sémin. Méditerr. 2008, 80, 267–274. Available online: http://om.ciheam.org/om/pdf/a80/00800451.pdf (accessed on 6 June 2019). Pedey, D.A. On indicators of droughts and wet conditions (in Russian). Proc. USSR Hydrometeorol. Centre Russian Meteorol. Hydrol. 1975, 156, 19–39 Saeid Eslamian , Kaveh Ostad-Ali-Askari , Vijay P. Singh , Nicolas R. Dalezios, Mohsen Ghane , Yohannes Yihdego, Mohammed Matouq. A Review of Drought Indices. International Journal of Constructive Research in Civil Engineering (IJCRCE) Volume 3, Issue 4, 2017, PP 48-66 ISSN 2454-8693 (Online) DOI: http://dx.doi.org/10.20431/2454-8693.0304005 www.arcjournals.org. Stadler, S.J. Aridity indexes. In Encyclopedia of World Climatology; Oliver, J.E., Ed.; Springer: Heidelberg,Germany, 2005; pp. 89–94. United Nations Educational, Scientific and Cultural Organization (UNESCO). Map of the World Distribution of Arid Regions: Map at Scale 1:25,000,000 with Explanatory Note; MAB Technical Notes 7; UNESCO: Paris, France, 1979. Vicente-Serrano, S.M., S. Begueria and J.I. Lopez-Moreno, 2010: A multi-scalar drought index sensitive to global warming: the Standardized Precipitation Evapotranspiration Index. Journal of Climate, 23:1696–1718. Zargar, A., Sadiq, R., Naser, B., & Khan, F. I. (2011). A review of drought indices. Environmental Reviews, 19(1), 333–349. https://doi.org/10.1139/a11-013
Keywords: посуха; характеристики посухи; індекс; метеорологічна посуха; drought; drought characteristics; index; meteorological drought